Changes in anthropometry and performance, and their interrelationships, across three seasons in elite youth rugby league players - Waldron, M.; Worsfold, P.; Twist, C.; Lamb, K. (The Journal of Strength and Conditioning Research, 2014)
This study investigated the changes in anthropometry and performance, and their interrelationships, across 3 consecutive seasons (under-15 to under-17 age groups) in elite youth rugby league players. Each player participated in annual anthropometrical and performance assessments, comprising measurements of stature; body mass; limb lengths and circumference; skinfolds; predicted muscle cross-sectional area (CSA); 20-m speed, countermovement jump height, vertical power, and aerobic power. Lean body mass percentage changed (p < 0.05) between the under-15 (70.9 ± 5.9%), under-16 (72.0 ± 5.8%), and the under-17 age groups (74.1 ± 5.7%). Likewise, predicted quadriceps muscle CSA also changed (p < 0.05) between each age group (under-15 = 120.9 ± 37.8 cm2; under-16 = 133.2 ± 36.0 cm2; under-17 = 154.8 ± 28.3 cm2). Concomitant changes between the under-15 and under-16 groups were found for 20-m speed (3.5 ± 0.1 cf. 3.4 ± 0.2 seconds; p = 0.008) and predicted jumping power (3,611.3 ± 327.3 W cf. 4,081.5 ± 453.9 W; p = 0.003). Both lean body mass and quadriceps muscle CSA consistently, related to both 20-m sprint time and jumping power, with r values ranging between -0.39 and -0.63 (20-m sprint time) and 0.55 to 0.75 (jumping power). Our findings demonstrate the importance of gains in lean body mass across later adolescence that support the ability to generate horizontal speed and predicted vertical power. This information informs the expectations and subsequent training programs of elite rugby league practitioners.